Non-Exosomal and Exosomal Circulatory MicroRNAs: Which Are More Valid as Biomarkers? - Nik Mohamed Kamal, Nik Nur Syazana Binti; Shahidan, Wan Nazatul Shima (Frontiers in Pharmacology, 2020)
MicroRNAs (miRNAs) are a group of small non-coding RNAs with approximately 19-25 nucleotides, involved in regulating a range of developmental and physiological processes. Non-exosomal circulating and exosomal miRNAs have also been proposed to be useful in diagnostics as biomarkers for diseases and different types of cancer. In this review, the quantity of miRNAs and reliable experimental data analysis of miRNA from the source of exosomal and non-exosomal miRNA are discussed for the use as biomarkers for cancer and other diseases, including viral infections, nervous system disorders, cardiovascular disorders and diabetes. We summarize other research findings of the use of miRNA from these two sources as biomarkers in diagnostics and clinical use. The challenges in using miRNA from these two sources in cancer and disease diagnostics are evaluated and discussed. Validation of specific miRNA signatures as biomarkers is a critical milestone in diagnostics.